Including food systems, biodiversity, nutrition and dietary health in the zero draft of the Post-2020 Global Biodiversity Framework: a joint submission from the Alliance of Bioversity International and the International Center for Tropical Agriculture (CIAT) (the Alliance), and the United Nations Environment Programme (UNEP) - Hunter, Danny; Souza Dias, Braulio de; Borelli, Teresa; DeClerck, Fabrice A.J.; Meldrum, Gennifer; Demers, Nicole R. (2020)
This paper is a joint submission by the Alliance of Bioversity International and the International Center for Tropical Agriculture (CIAT) (the Alliance), and the United Nations Environment Programme (UNEP), endorsed by: EAT; Food and Land Use Coalition (FOLU); Kenya Agricultural & Livestock Research Organisation (KALRO). As outlined in this paper, consideration of the proposed revisions to the Zero Draft can strengthen progress towards achieving the vision and goals of the Post-2020 Global Biodiversity Framework, while ensuring food and nutrition security for all people is achieved in an inclusive manner. This is based on sustainable, diverse and resilient food production systems that conserve and sustainably use biodiversity and its ecosystem services in agricultural and other managed ecosystems, as well as in natural ecosystems.